The effect of corporate social responsibility towards customer loyalty: the role of trust, c-c identification, and customer satisfaction - Halim, Rizal E; Hermawan, Ahmadan Maulana (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
In addition to running the rules set by the government, the activity of Corporate Social Responsibility (CSR) is also carried out by the company in increasing customer loyalty. This study aims to analyze the influence of CSR activities at the local aircraft company and local banking company to customer loyalty mediated by customer trust,C-C(Consumer-Company) identification, and customer satisfaction. Selection of these two industries because ofgrowththat hasoccurredeveryyear. The sample was consumers who have used the services of local aircraft in the last six months and consumers were registered as clients of local banks in the six months before the study began. This study uses Structural Equation Modeling (SEM) and found that for consumers from local aircraft, the company's CSR activities significantly affect customer loyalty through mediation of customer trust, while consumers fromÃ‚Â local bank, CSR activities significantly affect the customer loyalty through mediation of c-cidentification.